An investigation of e-services in developing countries : the case of e-government in Egypt - Hassan, H. S. H. (Cranfield University, 2011)
Many developing countries’ governments have invested heavily in e-service projects. However, there is a lack of clear case material research, which describes the potentialities experienced by governmental organisations. This research examines egovernment service projects and provides insights and learning into how to successfully develop and implement these projects within a developing country, specifically Egypt. The aim of this research is to develop a robust framework to support an efficient e-government system focusing on the case of Egypt. This is achieved by investigating selected completed and on-going successful initiatives and focusing on the barriers to, and the enablers of, these initiatives. As a result, the nature of successful e-governmental services initiatives is determined, and solutions to the possible emerging barriers and challenges are developed. Many lessons are learned to be taken into consideration in repeating the successful experience of other new eservice projects in the Egyptian government. A combination of research methodology approaches has been employed in this research. Firstly, an extensive review of literature took place to summarise and synthesise the arguments of the main factors contributing to the development of e-service research. Secondly, the qualitative approach and the case study are selected as an appropriate methodology for this research, using the semi-structured interview technique to gather data from top level officials who are involved in the Egyptian e-government program. Based on evidence, the cultural barriers group is the main group facing Egyptian e-government progress. On the other hand, the political will and enforcing decisions are the ultimate driving forces for the successful implementation of e-service projects in particular and the egovernment program in Egypt in general. Based on the findings, a framework is developed for explaining the main barriers and enablers of government e-service projects development, and providing solutions for the identified barriers, especially in a developing country environment like Egypt. Also, a process, of e-service projects implementation is proposed. A new enabler (decision enforcement) is found in the Egyptian government context and added to the list of enablers. From a practical point of view, this research provides realistic implications for the decision makers and officials within the Egyptian government involved in the process of planning, developing and implementing e-service projects.
Keywords: Developing Countries; E-government Program; Egyptian Government; E-service; Government to Citizens Projects